The Effect of the Web Based Digital Story Applications on the Digital Literacy Levels of Turkish Teacher Candidates - ÇOCUK, Halil Erdem; YELKEN, Tugba YANPAR (Asian Journal of Education and Training, 2018)
The technological developments that have directed 21st century skills have brought new content and dimension to narrative by integrating story narration, one of the earliest verbal narrative skills of mankind, with digital technology. The purpose of this study is to determine the effect of web-based digital story preparation on the literacy self-efficacy perceptions of Turkish teacher candidates in the digital media using pre-test, posttest, experimental-control group and semi-experimental design. A total of 60 teacher candidates, including 30 experimental groups and 30 control groups attending to the Teaching Principles and Methods Course in Mersin University Education Faculty Turkish Education Department participated in the study in 2016-2017 academic year. The research data were collected by the "Digital Media-Oriented Literacy Self-efficacy Scale" developed by the researchers. As a result of the study, Digital Media-Oriented Literacy Self-efficacy levels were observed to increased in both groups. However, a statistically significant difference was found only between pre-test and post-test scores of the self-efficacy perceptions of the Turkish teacher candidates who prepared a web-based digital story in the cooperative learning approach. It is suggested regarding the results of the study that in other studies, digital storytelling approach can be utilized by taking into consideration the content of both field and cultural courses, and also that researchers can investigate the effects of digital storytelling in terms of various variables.